Concepts of developing groups in team sports - Trninic, V.; Papic, V.; Dimec, T. (Acta Kinesiologica, 2008)
The success rate of a group's (team's) development concept mostly depends on management capabilities, the quality of professional work represented through team assembly, determining precise norms, roles and status of the group members (team players), selecting players for a specific position and role in the game, and forming an adequate game organisation. This is manifested in the way that the complete player's potential and actual quality is employed in the game tactics model. Team assembly, preparation and individual game management includes operative tactics, that is, anticipating possible occurences during the game, therefore anticipating possible actions and player substitutions. However, the concepts of group or team development should be grounded on combining a professional and scientific approach, which is evident in the integration of the subjective and objective estimates of the players and the entire team. The situation approach in the applied kinesiology is the most important because it is the base for the evaluation system of the player's potential and the team's and player's quality, as well as encouraging synchronized and collective team players' actions in the game. In modern sports games it would be optimal, in the concept of the team development and the competition success rate, to form a team with polyvalent players, as well as players that can efficiently play two or more positions both in the attack and defence phase. Bearing this in mind, it is also important that the manager knows how to form and insist upon the demands that are of the highest priority for the sport, as well as efficiently develop and enforce strategies for improving group cohesion. The manager's leadership capabilities of directing individuals and groups are today essential for team success.